Exploration of mathematical concepts in tek-tekan traditional games - Imaluddin Agus (Balai Diklat Keagamaan Ambon, 2023)
Exploration of mathematical concepts in tek-tekan traditional games is a form of student participation in acquiring knowledge directly. The purpose of this research is to find out the mathematical concepts contained in every aspect of tek-tekan traditional games starting from the aspects of the tools used, the players, the rules, and the stages or how to play. The research was conducted in class VII B MTsN 2 Konawe Selatan which was determined using a technique purposive sampling with consideration of the needs of this research where many students have played tek-tekan. Data collection methods consist of observation, interviews, and documentation. The results of this study indicate that there is a mathematical concept in tek-tekan traditional games. These mathematical concepts include a) comparison; b) distance, speed, and time; c) numbers and number arithmetic operations; d) corner; e) building space; f) possible combination, which appears in the tools used, game techniques, and how to play.